The clovehitch killer [videorecording (DVD)] - Skiles, Duncan; Skiles, Duncan; McDermott, Dylan; Plummer, Charlie, 1999-; Mathis, Samantha (Scream Factory, 2019)
A teenage boy discovers disturbing images in his father's possession and begins to suspect him of being the serial killer whose murders went unsolved in their community.